Pelatihan Peramalan Target Indikator Kinerja Daerah - Dara Puspita Anggraeni; Alfian Eka Utama; Rio Satriyantara; Irma Risvana Dewi (Rengganis Jurnal Pengabdian Masyarakat, 2023)
The purpose of this community service in the form of training is to improve the ability of functional planner staff in forecasting indicator targets of regional performance. This training is the continuation of (i) the training of using parametric statistic to increase the motivation of North Lombok Regency Bappeda's functional planner staff in research and scientific publications and (ii) the training of data processing using minitab for functional planner staff. This training was held on December 9, 2022, in BAPPEDA office in North Lombok Regency. The training participants were 6 functional planner staff. The method used in this training is providing a pre test, material deliverying, followed by practical forecasting of one of the regional performance indicators and ended with a post test. The material contains the definition of forecasting and several forecasting methods suitable for limited time series data including the Moving Average (MA) method, Simple Exponential Smoothing (SES) and the Naïve method, while the post test included the questions about the material given and the practice, also asked for suggestions, criticisms and themes for the further training. The effectiveness of the training will be tested with Wilcoxon Match Pairs test. The results of this training is the participants felt very helpful and proposed several themes for the next training. The results of the Wilcoxon Match Pairs test show that is greater than , meaning that the average post-test score is significantly higher than the average pre-test value or, in other words, community service in the form of training has an effect on the forecasting abilities of functional planner staff at North Lombok Regency's BAPPEDAThe purpose of this community service in the form of training is to improve the ability of functional planner staff in forecasting indicator targets of regional performance. This training is the continuation of (i) the training of using parametric statistic to increase the motivation of North Lombok Regency Bappeda's functional planner staff in research and scientific publications and (ii) the training of data processing using minitab for functional planner staff. This training was held on December 9, 2022, in BAPPEDA office in North Lombok Regency. The training participants were 6 functional planner staff. The method used in this training is providing a pre test, material deliverying, followed by practical forecasting of one of the regional performance indicators and ended with a post test. The material contains the definition of forecasting and several forecasting methods suitable for limited time series data including the Moving Average (MA) method, Simple Exponential Smoothing (SES) and the Naïve method, while the post test included the questions about the material given and the practice, also asked for suggestions, criticisms and themes for the further training. The effectiveness of the training will be tested with Wilcoxon Match Pairs test. The results of this training is the participants felt very helpful and proposed several themes for the next training. The results of the Wilcoxon Match Pairs test show that is greater than , meaning that the average post-test score is significantly higher than the average pre-test value or, in other words, community service in the form of training has an effect on the forecasting abilities of functional planner staff at North Lombok Regency's BAPPEDA